Antimicrobial interactions of Artemisia afra used in African traditional medicine - Suliman, Sajida (My University, 2012)
Many therapies prescribed by traditional healers in Southern Africa include plant combinations to treat infectious diseases. Artemisia afra is one of the most commonly used traditional medicines in African traditional medicine and most often given in combination with other plants. This plant‟s popularity coupled with its wide range of uses in combination serves as the rationale for the bases of this study. In this study, combinations of A. afra (essential oils and plant extracts), which are commonly used for the treatment of respiratory diseases were studied from an antimicrobial perspective in order to determine if a scientific basis exists for their combined use. The plants used often in double or triple combination with A. afra in the treatment of respiratory tract infections are Lippia javanica, Osmitopsis asteriscoides, Agathosma betulina, Eucalyptus globulus, Allium sativum, Leonotis randii, Tetradenia riparia and Zanthoxylum capense. Essential oils from plant samples were analysed using gas chromatography coupled to mass spectroscopy (GC-MS). Compounds found in highest concentrations were camphor (41.0%) in A. afra, linalool (70.7%) in L. javanica, 1,8-cineole (59.0%) in O. asteriscoides, isomenthone (31.4%) in A. betulina, 1,8-cineole (63.0%) in E. globulus and β-caryophyllene (32.4%) in T. riparia. Dichloromethane: methanol extracts and aqueous extracts were prepared for each plant using the dried ground plant material collected. The antimicrobial activities of each sample as well as each combination (including essential oils) were tested using the minimum inhibitory concentrations (MIC) assay against a panel of respiratory tract organisms. The highest sensitivities observed for the essential oils were that of E. globulus against Cryptococcus neoformans with a MIC value of 0.6 mg/ml. The dichloromethane: methanol extracts showed the most activity with E. globulus against Moraxella catarrhalis (MIC value of 0.01 mg/ml). The aqueous extracts showed the best activity with Z. capense against Streptococus agalactiae with a MIC value of 0.4 mg/ml. The 1:1 fractional inhibitory concentration (ΣFIC) values of the combinations of A. afra with L. javanica, A. afra with O. asteriscoides, A. afra with A. betulina, A. afra with E. globulus and A. afra with Z. capense were calculated from the MIC data. Synergy, additivity, indifference and antagonistic interactions within the combinations were then interpreted. The most significant interactions of the double combinations with synergistic ΣFIC values of 0.2 were the combination of the dichloromethane: methanol extracts of A. afra with O. asteriscoides against Streptococcus pyogenes and the combination of the aqueous extracts of A. afra with E. globulus against Streptococcus pneumoniae. Significant antagonism was noted with the combination of the dichloromethane: methanol extracts of A. afra with E. globulus against Enterococcus faecalis. The ΣFIC results of the combinations of A. afra with L. javanica, O. asteriscoides, A. betulina, E. globulus or with Z. capense were used to calculate ratios and plotted on to an isobologram. The isobolograms were interpreted with regard to any synergy, antagonism, or additive interactions present in the combination. Isobolograms revealed the most significant activity with the combination of the aqueous extracts of A. afra with E. globulus against C. neoformans with all the ratios tested being synergistic. The most prominent antagonism (five ratios) noted was in the combination (dichloromethane: methanol extracts) of A. afra with E. globulus against M. catarrhalis. The triple combinations analyzed for their antimicrobial activity were the combinations of A. afra with O. asteriscoides and E. globulus, A. afra with L. randii and E. globulus, A. afra with A. sativum and Z. capense and the combination of A. afra with T. riparia and salt. The most significant synergistic activity was noted for the combination of the essential oils A. afra with T. riparia and salt against Mycobacterium smegmatis with a ΣFIC value of 0.2. The combination of A. afra with O. asteriscoides and E. globulus of (dichloromethane: methanol extracts) displayed the most antagonistic activity against M. catarrhalis. When analysing the combinations that include A. afra, it was noted that adjuncts are an important combination ingredient in the traditional method of preparation. These were also tested for their activity. The combinations that include adjuncts i.e. honey, salt, vinegar, brandy and milk showed mainly indifferent interactions. This indifference noted supports the use of these adjuncts by traditional healers as it serves to verify that these adjuncts are at least not hindering the activity of the plant itself, which is a positive direction for future investigations. Traditional medicine, with regard to A. afra, as prescribed by traditional healers, has commonly employed the use of combinations of more than one plant to treat respiratory conditions. When the antimicrobial activities in combination were examined from a scientific viewpoint, there is evidence of some bases for their traditional use. The results obtained from the testing of the essential oils validate its traditional use as an inhalant. The dichloromethane: methanol extracts showed results varying from synergy to antagonism while the aqueous extracts showed good antimicrobial activity. It is recommended that future studies should be conducted into these interactions to determine the benefits of these combinations for possible use in the commercial and primary health-care sectors.
Keywords: Artemisia afra; Plants, Medicinal